2005
DOI: 10.1051/0004-6361:20041961
|View full text |Cite
|
Sign up to set email alerts
|

The VIMOS-VLT deep survey

Abstract: Abstract. We investigate the evolution of the galaxy luminosity function from the VIMOS-VLT Deep Survey (VVDS) from the present to z = 2 in five (U, B, V, R and I) rest-frame band-passes. We use the first epoch VVDS deep sample of 11 034 spectra selected at 17.5 ≤ I AB ≤ 24.0, on which we apply the Algorithm for Luminosity Function (ALF), described in this paper. We observe a substantial evolution with redshift of the global luminosity functions in all bands. From z = 0.05 to z = 2, we measure a brightening of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
339
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(366 citation statements)
references
References 32 publications
26
339
1
Order By: Relevance
“…The TSR is the number of targets that were allocated a slit for spectroscopic observation divided by the number of photometric targets down to an apparent magnitude limit. The TSR depends on RA, DEC, magnitudes and for VVDS on the size of the galaxy along the spatial dimension of the slit (see Ilbert et al 2005). The SSR is the fraction of spectroscopic targets for which the redshift was successfully determined.…”
Section: Sampling Rate Correctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TSR is the number of targets that were allocated a slit for spectroscopic observation divided by the number of photometric targets down to an apparent magnitude limit. The TSR depends on RA, DEC, magnitudes and for VVDS on the size of the galaxy along the spatial dimension of the slit (see Ilbert et al 2005). The SSR is the fraction of spectroscopic targets for which the redshift was successfully determined.…”
Section: Sampling Rate Correctionsmentioning
confidence: 99%
“…Furthermore, we bin the data in narrow redshift bins, and therefore, we neglect the variation of TSR with galaxy size. VVDS-Deep TSR and SSR are provided through their data base (see Ilbert et al 2005, for more details). For the VVDS-Wide and DEEP2, we compute them as follows.…”
Section: Sampling Rate Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute magnitudes are computed following the method described in the Appendix of Ilbert et al (2005). The K-correction is computed using a set of templates and all the multi-band photometry data available.…”
Section: Stellar Masses and Absolute Magnitudes Estimatementioning
confidence: 99%
“…The LFs are computed using the "Algorithm for Luminosity Function" (ALF, Ilbert et al 2005). Ilbert et al (2004) demonstrated that the estimate of the global LF can be biased when the band used to compute the LF strongly differs from the rest-frame band in which the galaxies are selected.…”
Section: Resultsmentioning
confidence: 99%